RUSSIAN EPIGRAPHIC MEMORIAL INSCRIPTIONS OF THE 19TH CENTURY IN VILNIUS CATHOLIC GRAVEYARDS - Tolkačevski, Kšištof (Knygotyra, 2016)
The article is aimed at the analysis of 19th century epitaphs, inscribed in the Russian language in Vilnius Catholic graveyards, treating the epitaphs as a source of interdisciplinary research. Back then, it was common practice to engrave epitaphs in Catholic cemeteries in Polish and Latin languages. Occasionally, epitaphs in French and German languages were engraved on the tombs of the persons having respective nationalities. The Polish language was prevailing on the Lithuanian territory in the 19th century as a language universally used by representatives of a certain cultural layer, that is, the Catholics, both Poles and Lithuanians. The article presents an analysis of epigraphic memorial inscriptions in Vilnius churchyard burial grounds (St. Stephen, St. Jacob and St. Philip) and the graveyards outside the city limits (Rasos, the Bernadines’ and St. Raphael). The analysis is based on the copies of tombstone epitaphs compiled in 1885 by the collector and a prominent figure in the field of culture Albert Ludwik Zasztowt (1850–1918), stored in the Wroblewski library of the Lithuanian Academy of Sciences, and the catalogue of the persons buried in Vilnius graveyards, created by Wacławo Wejtko (1861–1939). The author sought to reconstruct Russian epigraphic memorial inscriptions in Vilnius graveyards (given in the Annex). In total, 26 inscriptions have been identified. During the research, the traditional and most common Catholic epitaph of the 19th has broken down into structural elements. These elements are further defined in order to identify their functions, as part of the text. On the basis of such findings, the text structure of Russian inscriptions is then researched. In such a way, light is shed on the elements of the texts inscribed in Cyrillic script from a semiotic point of view. The article also presents an analysis of the historic context of the emergence of such a source and changes in the use of language in the end of the 19th century. Furthermore, the article aims at identifying the links between biographistics and keeping alive the memory as well as analysing the relationship between the text creator and the reader.
Keywords: ...